Renal Artery Pseudoaneurysm Following Laparoscopic Partial Nephrectomy - Shapiro, Edan Y.; Ari Hakimi, A.; Hyams, Elias S.; Cynamon, Jacob; Stifelman, Michael; Ghavamian, Reza (Urology (Ridgewood, N.J.), 2009)
To present our experience with the management of renal artery pseudoaneurysms following laparoscopic partial nephrectomy (LPN). Our bi-institutional LPN database of 259 patients from July 2001 to April 2008 was queried for patients diagnosed with a postoperative renal artery pseudoaneurysm. Demographic data, perioperative course, complications, and follow-up studies in identified subjects were analyzed. Postembolization success was defined as symptomatic relief, resolution of hematuria, and a stable hematocrit and serum creatinine. We identified 6 patients (2.3%) who were diagnosed with a renal artery pseudoaneurysm after LPN. The mean age of our cohort was 61.2 years (49-76), mean operative time was 208 minutes (140-265), and mean estimated blood loss was 408 mL (50-800). Patients presented at a mean of 12.6 days (5-23) after the initial surgery. Five patients had gross hematuria and a decreased hematocrit, with 1 patient presenting with clinical symptoms of hypovolemia. The sixth patient was incidentally diagnosed. The diagnosis of a renal artery pseudoaneurysm was confirmed in all cases by angiography. Selective angioembolization was successfully performed in all patients. At a median follow-up of 8.3 months all patients (100%) remained without any evidence of recurrence. Although pseudoaneuryms are a rare postoperative complication of LPN, they are potentially life-threatening. Early identification and proper management can help reduce the potential morbidity associated with pseudoaneurysms. Our experience demonstrates the feasibility and supports the use of selective angioembolization as an excellent first-line option for patients who present with this form of delayed bleeding.